Holding both truths: Early dynamics of ethnic‐racial socialization and children's behavior adjustment in African American and Latinx families. (25th December 2021) - Contreras, Mariah M.; Osborne, Kimberly R.; Walsdorf, Ashley A.; Anderson, Leslie A.; Caughy, Margaret O'Brien; Owen, Margaret Tresch
Abstract: Ethnic‐racial socialization is at the core of ethnic minority families' adaptive response to a racialized social climate. Protective links between ethnic‐racial socialization and children's adjustment are well documented in the adolescent years; however, very few studies have considered the ethnic‐racial socialization of young children altogether and fewer still have examined the links to adjustment using longitudinal designs. Leveraging unique, longitudinal data, the present study modeled African American and Latinx caregivers' emergent use of multiple ethnic‐racial socialization strategies across the critical period when children first enter school, testing how their strategies dynamically interplay with children's early behavior adjustment. Results indicated an early pathway in which a child's behavior adjustment problems at 2.5 years may cascade to caregivers' use of preparation for bias strategies at 3.5 years which in turn may modestly spillover in children's behavior adjustment in kindergarten. There was also modest evidence that cultural socialization strategies used in kindergarten may serve a protective function for future behavior adjustment. The potential to develop and extend interventions around both systemic issues and the direct needs of families is discussed.